A combined behavioural economics- and simulation-based medical education to promote effectiveness among medical residents in coping with workplace violence in Northern China: a quasi-experimental study - Chao Liu; Weijing Liu; Mingli Jiao; Ye Li; Gangyu Zhang; Lifeng Wei; Shuang Zhou; Yuanheng Li; Zhuowa Sha; Yanhua Hao; Qunhong Wu (BMC, 2022)
Abstract Background Workplace violence is internationally recognised as a major concern for the workforce, which entails serious consequences, and research shows that medical residents are more likely than other doctors to experience violence in the workplace. This study first examines the effectiveness of simulation-based medical education, and then simulation-based medical education combined with behavioural economics as interventions in medical residents' perception of, attitude toward, and self-efficacy in coping with violence in the workplace. Methods A quasi-experimental design was used, 190 participants were randomised into three study groups to respectively test the effect of simulation-based medical education only and simulation-based medical education plus behavioural economics interventions, compared with a control group. Data were obtained from structured questionnaires, including (1) a perception of aggression scale, a management of aggression and violence attitude scale, a general self-efficacy scale, and (2) socio-demographic characteristics. Results The results show that the scores attained by simulation-based medical education (SBME) and simulation-based medical education combined with behavioural economics (SBME + BE) interventions for perception, attitude, and self-efficacy were significantly higher than those in the control group (p < .01). The SBME + BE group recorded a greater improvement in perception, which could be ascribed to the behavioural economics effect. Furthermore, the higher perception of workplace violence is correlated with single residents and those with more work experience, prior experiences of violence in the workplace, and training related to workplace violence. A higher positive correlation of workplace violence was recorded by female and widowed residents,and a higher level of self-efficacy related to violence in the workplace correlated with male, widowed,and senior (third-year) residents. Conclusions This study contributes important evidence regarding changes in the perception, attitude, and self-efficacy of subjects following both the SBME + BE and SBME interventions among medical residents in coping with workplace violence, the biggest perception change having been recorded after the SBME + BE intervention, which can be explained by the inclusion of behavioural economics.